Multiwavelength Brillouin/Erbium-Ytterbium fiber laser - Harun, Sulaiman Wadi; Emami, Siamak Dawazdah; Rahman, Faidz Abd; Muhd-Yassin, Shahrin Zen; Abd-Rahman, Mohd Kamil; Ahmad, Harith (John Wiley & Sons, 2013)
A multi-wavelength Brillouin/Erbium-Ytterbium doped fiber laser which operates in the 1535 nm region is proposed and demonstrated. The system employs both linear and nonlinear gain from a 4 meter Erbium-Ytterbium doped fiber and an 8 km single mode fiber respectively to generate an optical comb with a spacing of approximately 0.084 nm. A stable output laser comb of more than 22 lines was obtained with a Brillouin pump of 2 dBm and a 1058 nm pump of 175 mW. A maximum peak power of -4.2 dBm was obtained at a wavelength of 1535.16 nm at these pump power settings while the spectral linewidth of the laser is approximately 8 Hz. A graph is presented. Peak power for various lines as a function of 1058 nm pump power.